Association Between Stress Levels, BMI, and Menstrual Cycle Regularity Among Female University Students - Hambarsika, I Gusti Ayu Komang Esti Purnami; Vitalistyawati, Luh Putu Ayu; Putri, Ni Made Rininta Adi; Sari, Ni Luh Made Reny Wahyu (Interest : Jurnal Ilmu Kesehatan, 2025)
Background: The menstrual cycle functions through a coordinated balance of reproductive hormones. An imbalance in these reproductive hormones can disrupt the menstrual cycle. Aspects that can impact the menstrual cycle include stress and BMI. This study aimed to assess the association between stress levels and BMI on the menstrual cycle among female university students  Methods: This research used a cross-sectional study conducted at Dhyana Pura University from April 2025 to May 2025. A total of 40 respondents participated in this study with purposive sampling. Data collection of stress level using the PSS-10 questionnaire, BMI using Staturemeter and digital scales, and menstrual cycle with tracking application (FLO). Pearson correlation test for stress and menstrual cycle variables, Spearman’s Rho for BMI and menstrual cycle variables, and multiple linear regression test. A Significance level of p<0.05 was used. Results: The association between stress levels and menstrual cycle showed a p-value of 0.13 (p < 0.05). The relationship between BMI and menstrual cycle showed a p-value of 0.411 (p>0.05). The relationship between stress level and BMI on menstrual cycle showed a p-value of 0.44 (p < 0.05) with an R-squared value of 0.395. This indicates a weak-to-moderate correlation between stress level and BMI on the menstrual cycle. Conclusion: This demonstrates a relationship between stress level and BMI on the menstrual cycle, with a weak-to-moderate strength. Based on these findings, students are encouraged to manage their stress levels and maintain a healthy BMI to support regular menstrual cycles.